(untitled) - Dobermann, Achim (Oxford, 2000)
This hanbook provides a guide for detecting nutrient deficiency and toxicity symptoms, and managing nutrients in rice grown in tropical regions. Some background information on the function of nutrient in rice and the possible causes of nutrient deficiencies.
Keywords: Plants,Rice,Dinh dưỡng cho lúa gạo; Nutrition,Nutrition